Comparison of fracture site callus with iliac crest bone marrow as the source of plastic-adherent cells (Medical Journal of Indonesia, 2013)
Background: Red marrow has been described as the main source of mesenchymal stem cells although its aspiration and isolation from bone marrow was reported to have significant donor site morbidity. Since secondary bone healing occurs through formation of callus as the result of proliferation and differentiation of mesenchymal stem cells, callus may become alternative source for mesenchymal stem cells. In this study, we compared the number of plastic-adherent cells from fracture site callus and bone marrow of iliac crest after two and four weeks of culture. Methods: Sixteen New Zealand rabbits were fracturized at the femoral shaft. Then, these rabbits were taken care. After two weeks of fracturization, 3 mL iliac crest bone marrow aspiration and callus extraction of eight rabbits were cultured (group I). The other eight rabbits were treated equally after four weeks of fracturization (group II). Simultaneously, the cultures were observed after one and two weeks. Four weeks later, they were harvested. Cells were counted using Neubauer hemocytometer. The average number of cells between the sources and groups were statistically analyzed using the unpaired t-test. Results: In group I, there were 2.6±0.1 x 104 cells in the culture of iliac crest bone marrow aspirate and 2.5 ± 0.1 x 104 cells in culture of callus extract from fracture site (p=0.34). In group II, there were 2.7 ± 0.1 x 104 cells and 2.1 ± 0.1 x 104 cells, respectively (p < 0.001). Conclusion: Fracture site callus at the second week post-fracturization may be potential as source of plastic-adherent cells compared with iliac crest bone marrow.